A dynamic replication management strategy in distributed GIS. (March 2018) - Pan, Shaoming; Xiong, Lian; Xu, Zhengquan; Chong, Yanwen; Meng, Qingxiang
Abstract: Replication strategy is one of effective solutions to meet the requirement of service response time by preparing data in advance to avoid the delay of reading data from disks. This paper presents a brand-new method to create copies considering the selection of replicas set, the number of copies for each replica and the placement strategy of all copies. First, the popularities of all data are computed considering both the historical access records and the timeliness of the records. Then, replica set can be selected based on their recent popularities. Also, an enhanced Q-value scheme is proposed to assign the number of copies for each replica. Finally, a reasonable copies placement strategy is designed to meet the requirement of load balance. In addition, we present several experiments that compare the proposed method with techniques that use other replication management strategies. The results show that the proposed model has better performance than other algorithms in all respects. Moreover, the experiments based on different parameters also demonstrated the effectiveness and adaptability of the proposed algorithm. Highlights: A comprehensive model for dynamic replication management is proposed. The new model considers the timeliness of historical records. An enhanced Q-value scheme is proposed to avoid unfair initialization. The proposed model can quickly track the changes of access patterns.